' … a Tasteful Decoration of the Crematory, without any Distracting Content and Meaning.' The Exhibition Klar Form in 1951 and the Dispute on the Potential of Abstract Art. (2nd January 2020) - Højsgaard, Mette
Summary: An abstract follows here, if needed: In December 1951 the exhibition Klar Form opened in Copenhagen. It was the first venue of a Scandinavian tour that included Oslo, Stockholm and Helsinki. It was organized by the prolific Galerie Denise René, Paris in collaboration with the Galerie Børge Birch, Copenhagen and the Danish artists Richard Mortensen and Robert Jacobsen. The exhibition showed a mixture of the pioneers of abstract art such as Le Corbusier and Fernand Léger, and the younger generation including artists such as Victor Vasarely, Jean Dewasne, Robert Jacobsen, Richard Mortensen and Serge Poliakoff. Klar Form could be seen as an art political statement meant to strengthen the impact of geometrical abstract art and has gained a place in Danish art history as a crucial exhibition with great influence on the subsequent development of the abstract art of the 1950s. However, the critique of Klar Form in the Danish press was far from univocally positive. Instead, as the sharply negative voices reveal, the exhibition was the object of fierce debate based on a broader underlying debate on cultural politics in the early years of the Cold War and on art in society. This article focusses on these negative voices in an attempt to reveal new aspects of this debate.